Residential self-selection in quasi-experimental and natural experimental studies: An extended conceptualization of the relationship between the built environment and travel behavior - Eva Heinen; Bert van Wee; Jenna Panter; Roger Mackett; David Ogilvie (Journal of Transport and Land Use)
Despite a large body of research suggesting that the built environment influences individual travel behavior, uncertainty remains about the true nature, size, and strength of any causal relationships between the built environment and travel behavior. Residential self-selection, the phenomenon whereby individuals or households select a residential area based on their transport attitudes, is a frequently proposed alternative explanation for the reported associations. To resolve the issue of residential self-selection, longitudinal studies are often recommended. In this paper, we argue that intervention study designs are insufficient to fully resolve the problem and that intervention studies on the built environment and travel behavior may still be biased by residential self-selection. The aim of this paper is to extend existing conceptualizations of the relationships between the built environment, travel behavior, and attitudes and to provide suggestions for how a causal relationship between the built environment and travel behavior may be ascertained with more accurate estimates of effect sizes. We discuss the complexities of determining causal effects in intervention studies with participants who relocate, and the biases that may occur. We illustrate the complexities by presenting extended conceptualizations. Based on these conceptualizations, we provide considerations for future research. We suggest repeating analyses with and without individuals who relocated during the study, and with and without statistical controls for residential relocation. Additional quantitative and qualitative analyses will be necessary to obtain more accurate effect size estimates and a better understanding of the causal relationships.